Ecophysiology of halophytes: questions and challenges - Shabala, Sergey (Ecological Questions, 2011)
Halophytes are able to tolerate and even benefit from salt concentrations that kill most other plant species and, at the very least, may provide genes that allow transgenic conference of salinity tolerance to crops. In addition, some halophytes have already been tested as vegetable, forage and oilseed crops. However, physiological mechanisms behind the remarkable ability of halophytes to live in highly saline environment are not fully understood. This talk highlights some unanswered questions and challenges in understanding halophyte physiology, with a specific emphasis on complexity of plant-environmental interaction.